Association between body mass index and outcome in Japanese ischemic stroke patients. Issue 3 (22nd January 2016) - Kawase, Shinya; Kowa, Hisanori; Suto, Yutaka; Fukuda, Hiroki; Kusumi, Masayoshi; Nakayasu, Hiroyuki; Nakashima, Kenji
Abstract : Aim: An association between body mass index (BMI) and stroke outcome have been reported, but the results are controversial. The aim of the present study was to evaluate whether BMI is associated with ischemic stroke outcome. Methods: Consecutive Japanese acute ischemic stroke patients were analyzed. BMI was categorized as underweight (BMI <18.5 kg/m 2 ), normal weight (18.5–24.9 kg/m 2 ) and obese (≥25 kg/m 2 ). BMI and short‐term and long‐term outcomes were examined. Short‐term outcomes were evaluated using the modified Rankin scale score at hospitalization and discharge; modified Rankin scale ≥3 was defined as a poor outcome. Long‐term outcomes were evaluated by all‐cause mortality. The recurrence rate was also evaluated in each BMI group. Values of P  < 0.05 were considered significant. Results: A total of 1206 acute ischemic stroke patients (760 men; mean age 72.5 years) were analyzed in the present study. There were 111 underweight cases (9.2%), 785 normal weight cases (65.1%) and 310 obese cases (25.7%). The underweight group had a significantly higher rate of poor short and long‐term outcomes than the normal weight group. The outcomes of the obese group were not significantly different from those of the normal weight group. Recurrence was not significantly different among the groups. Conclusions: Lower BMI might be a predictor of poorer short‐term and long‐term stroke outcomes.Geriatr Gerontol Int 2017; 17: 369–374.